BIOLOGICAL MECHANISMS OF OSSEOINTEGRATION OF DENTAL IMPLANTS (LITERATURE REVIEW) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The increasing popularity of dental implantation as a method of oral rehabilitation has attracted significant scientific attention to the mechanisms of interaction between implants and bone tissue. The purpose of this review is to evaluate and systematize both domestic and international research data concerning the osseointegration of titanium dental implants.
Keywords: Analysis of recent scientific literature demonstrates that advances in research methodologies and the introduction of interdisciplinary approaches have considerably transformed conventional understanding of osseointegration.